2002
DOI: 10.1136/oem.59.8.517
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcome among female hairdressers

Abstract: Background:Working as a hairdresser involves exposure to a variety of chemical agents.Aims:To estimate the risk of such exposure in relation to reproductive outcome.Methods:A cohort of hairdressers, certified in Sweden from 1970 onwards, and a referent cohort of women from the general population were established and linked to the Swedish Medical Birth Register for the period 1973 to 1994. In the cohort of hairdressers 3706 women gave birth to 6960 infants. The corresponding numbers among the referents were 346… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 18 publications
3
55
1
2
Order By: Relevance
“…The findings for low birthweight and small for gestational age in our study are partly in agreement with previous findings (21,22). In the study from The Netherlands, the authors stated that the risk had decreased over time, and they thought that this decrease may be a result of exchanging the toxic agents in the beauty salons for less hazardous ones (21).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The findings for low birthweight and small for gestational age in our study are partly in agreement with previous findings (21,22). In the study from The Netherlands, the authors stated that the risk had decreased over time, and they thought that this decrease may be a result of exchanging the toxic agents in the beauty salons for less hazardous ones (21).…”
Section: Discussionsupporting
confidence: 82%
“…About 25% of the hairdressers in our study were also included in a former study of Swedish hairdressers (22). When the analyses in our study were restricted to the hairdressers who were not included in the former study, the results did not change more than marginally.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Some studies report that female hairdressers have an increased risk of having children with major malformations such as hypospadias (15)(16)(17) while others find no support for an increased risk (18)(19)(20). Thus, studies have been conflicting, and -so far -no health problems related to reproduction and fetal development have been identified among hairdressers (21).…”
Section: Jørgensen Et Almentioning
confidence: 93%
“…Although hairdressers as a group displayed a 2.7-fold increase in risk, this did not reach statistical significance (33). Two Swedish cohort studies have assessed the reproductive outcomes of hairdressers and found a relative risk of 1.3 of major malformations, including hypospadias, in a study from 2002 but found no association in a more recent study from 2005 (17,18).…”
Section: Jørgensen Et Almentioning
confidence: 99%